Pengaruh Intellectual Capital dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Intervening (Studi Kasus Pada Perbankan Yang Terdaftar di BEI Tahun 2017-2021): (Studi Kasus Pada Perbankan Yang Terdaftar di BEI Tahun 2017-2021) - Alveno Prakoo Nugroho; Risal Rinofah; Ratih Kusumawardhani (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This study aims to determine the impact of intellectual capital and size on the value of banking companies listed on the Indonesian stock exchange during the period 2017-2021, with the intervention variable being financial performance. This study uses a quantitative method. This study includes all companies listed on the Indonesia Stock Exchange from 2017 to 2021, using a sampling method. This study used SPSS v22 multiple regression and path analysis methods. The results of this study show that: The effect of capital on firm value can be reduced by including financial performance as a secondary variable; the effect of size on value cannot be reduced by using financial performance as a secondary variable.